Environment-friendly high-temperature-resistant refractory brick and preparation method thereof

By combining modified fly ash with composite binders and employing a gradient sintering process, the problem of insufficient performance of refractory bricks at high temperatures has been solved, achieving improvements in high-temperature strength and oxidation resistance, reducing production energy consumption, and meeting the needs of green industrial development.

CN121673028APending Publication Date: 2026-03-17HEBEI JIENENG REFRACTORY (GRP) CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202512002713.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-29
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing refractory bricks have insufficient performance at high temperatures, making it difficult to simultaneously meet the requirements of environmental protection and performance under extreme high temperatures. Furthermore, the production process is hampered by bottlenecks such as uneven raw material dispersion, high sintering energy consumption, and persistently high costs.

Method used

Modified fly ash, zirconium oxide, composite binder, and low-temperature sintering process are used. By modifying fly ash and lime slag together, and combining it with a composite binder of molybdenum dinitride and phenolic resin, and with a gradient sintering process, the density and oxidation resistance of the brick structure are improved.

Benefits of technology

This has improved the high-temperature strength and oxidation resistance of refractory bricks, reduced production energy consumption, optimized material utilization and cost, and met the needs of green industrial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121673028A_ABST
    Figure CN121673028A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and particularly relates to an environment-friendly high-temperature-resistant refractory brick and a preparation method thereof. The environment-friendly high-temperature-resistant refractory brick is prepared from the following raw materials in percentage by weight: 12 to 15 weight percent of crystalline flake graphite, 8 to 12 weight percent of modified fly ash, 1 to 3 weight percent of zirconium oxide, 5 to 8 weight percent of composite binder and the balance of magnesium oxide, the modified fly ash is prepared by the following preparation processes: adding fly ash into a nitric acid solution, stirring, filtering, washing and drying to obtain active fly ash; adding the active fly ash, a surfactant and scandium chloride into water, adjusting the pH value at 50-60 DEG C, standing, filtering, washing and drying to obtain scandium modified fly ash; ball-milling and mixing the scandium modified fly ash, lime slag and triethanolamine, and calcining to obtain the modified fly ash. The refractory brick disclosed by the invention has excellent compression strength, high-temperature fracture resistance and excellent oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of refractory materials, and particularly relates to an environmentally friendly high-temperature-resistant refractory brick and a preparation method thereof. BACKGROUND

[0002] China is a large country with the world's first output of high-temperature industries such as steel, electricity, petrochemicals, and building materials. As a refractory ceramic material, refractory bricks are often used in high-temperature fields, and their performance is directly related to the production efficiency and operational safety of high-temperature industries. However, traditional refractory bricks are mostly made of clay, corundum, etc. as raw materials, which not only destroys the ecology during mining, but also easily releases harmful gases such as SO2, NO X , etc. during high-temperature use, and is difficult to degrade after being discarded, forming a large amount of industrial solid waste. In addition, traditional bricks also have defects such as limited high-temperature resistance, poor thermal stability, and short service life, and frequent replacement not only increases production costs, but also exacerbates resource consumption and environmental pollution, which is in serious conflict with the concept of green industrial development. Therefore, developing new refractory bricks with excellent high-temperature resistance, long service life, and environmental friendly characteristics has become the key to resolving the contradiction between environmental pressure and high-performance requirements in the high-temperature field of industry.

[0003] Existing environmentally friendly refractory bricks are mainly improved along two paths: one is to use industrial solid waste to prepare, which reduces raw material consumption, but often has problems of insufficient high-temperature strength and erosion resistance; the other is to use organic environmentally friendly binders, but they are easily decomposed at high temperatures above 1600℃, leading to failure of the brick structure. The current solutions are difficult to meet the requirements of environmental friendliness and performance at extremely high temperatures at the same time, and there are generally bottlenecks such as uneven distribution of raw materials, high sintering energy consumption, and high costs in production, which restrict their large-scale application and promotion.

[0004] To effectively balance the high-temperature resistance, strength, and environmental friendliness of refractory bricks, material innovation and process optimization should be combined. Specifically, high-performance environmentally friendly raw materials should be selected and compounded, and the utilization value of industrial solid waste should be improved through modification technology; at the same time, energy-saving processes such as low-temperature sintering and microwave sintering should be actively used to reduce energy consumption and thereby improve the uniformity and density of the brick structure. These comprehensive means are the only way to promote the upgrading of the refractory materials industry towards green, efficient, and sustainable direction. SUMMARY

[0005] The first object of the present application is to provide an environmentally friendly high-temperature-resistant refractory brick, which has excellent compressive strength, high-temperature bending performance, and excellent oxidation resistance.

[0006] The second object of the present application is to provide a preparation method of the above-mentioned environmentally friendly high-temperature-resistant refractory brick.

[0007] To achieve the above-mentioned objects, the technical solution adopted by the present application is: An environment-friendly high-temperature-resistant firebrick is prepared from the following raw materials in percentage by weight: flake graphite 12-15 wt%, modified fly ash 8-12 wt%, zirconia 1-3 wt%, composite binder 5-8 wt%, and the balance being magnesia; The modified fly ash is prepared by the following process: (1) stirring fly ash in a nitric acid solution, filtering, washing, and drying to obtain active fly ash; (2) adding the active fly ash, a surfactant, and scandium chloride into water, adjusting pH at 50-60 ℃, standing, filtering, washing, and drying to obtain scandium-modified fly ash; (3) ball-milling the scandium-modified fly ash, lime residue, and triethanolamine, and calcining to obtain the modified fly ash.

[0008] Further, in step (1), the mass ratio of the fly ash to the nitric acid solution is 1:3-5, and the concentration of the nitric acid solution is 1-1.2 g / mL.

[0009] Further, in step (2), the mass ratio of the active fly ash, the surfactant, and scandium chloride is 1:(0.02-0.05):(0.1-0.2), the surfactant is dodecyltrimethylammonium bromide, the pH is adjusted to 6-7, and the standing time is 1-2 h.

[0010] Further, in step (3), the mass ratio of the scandium-modified fly ash, lime residue, and triethanolamine is 1:(0.08-0.1):(0.03-0.05), the calcination temperature is 600-700 ℃, and the calcination time is 2-3 h.

[0011] Further, the composite binder is prepared by the following process: (a) adding trizinc dinitride and polydimethylsiloxane into methanol for ultrasonic treatment, and heating and distilling to obtain modified trizinc dinitride; (b) mixing and stirring the modified trizinc dinitride and phenolic resin to obtain the composite binder.

[0012] Further, in step (a), the amount ratio of the trizinc dinitride to polydimethylsiloxane is 1 g:15-20 mL, and the heating and distilling temperature is 90-100 ℃.

[0013] Further, in step (b), the mass ratio of the modified trizinc dinitride to phenolic resin is 1:(5-8), and the phenolic resin is thermosetting phenolic resin.

[0014] The above-mentioned preparation method of the environment-friendly high-temperature-resistant firebrick comprises the following steps: Magnesium oxide, flaky graphite, zirconium oxide and modified fly ash are mixed uniformly, then a composite binder is added and mixed uniformly, and then the mixture is loaded into a mold for pressure preservation to obtain a brick blank; the brick blank is gradient sintered, and the environmental protection type high-temperature-resistant refractory brick is obtained after cooling.

[0015] Further, the pressure for pressure preservation is 200-250 MPa, and the time is 3-5 min.

[0016] Further, the process of gradient sintering is: first sintering at 220-280 DEG C for 5-8 h, then heating to 700-750 DEG C for sintering for 3-5 h, and then heating to 1300-1400 DEG C for sintering for 2-3 h.

[0017] The beneficial technical effects of the present application are: 1. The modified fly ash is added in the refractory brick, which not only realizes efficient utilization of industrial waste fly ash, but also optimizes the sintering density of the refractory brick and improves the high-temperature resistance and oxidation resistance. The fly ash has a high specific surface area and gel activity, and after being modified by scandium chloride and lime slag, the alkaline substances in the lime slag can activate the activity of the fly ash and react with the silicon dioxide and aluminum oxide therein to form a high-temperature-resistant mineral phase; the scandium chloride loaded on the fly ash can further improve the gel activity of the fly ash, optimize the microstructure of the fly ash, purify impurities, reduce the porosity, enhance the bonding force between the fly ash and the refractory brick matrix, improve the sintering density, and improve the high-temperature strength and oxidation resistance.

[0018] 2. The present application uses a composite binder of tri-molybdenum dinitrogen and phenolic resin, and cooperates with the improved segmented sintering process to improve the sintering quality of the refractory brick and improve the mechanical properties and oxidation resistance. At a low temperature stage, the phenolic resin starts to pyrolyze under the catalysis of tri-molybdenum dinitrogen to form an ordered graphitization network to strengthen the bonding effect; at a medium temperature stage, the tri-molybdenum dinitrogen reacts with the matrix to form carbide to enhance the interfacial bonding force and strengthen the bonding phase network to improve the sintering quality; at a high temperature stage, the molybdenum compound forms a dense and stable oxidation-resistant layer and forms a pinning effect in the matrix to improve the mechanical properties of the refractory brick. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 The scanning electron microscope image of the modified fly ash prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0020] The following further describes the present application in connection with specific preferred embodiments, which should not be construed as limiting the present application to these specific embodiments. Those skilled in the art will readily understand that the present application is well adapted to carry out several similar embodiments without departing from the spirit and scope of the present application. The specific conditions not mentioned in the examples are carried out according to the conventional conditions or the conditions recommended by the manufacturers. The reagents or instruments used are conventional products available in the market, unless otherwise specified.

[0021] (I) Examples Example 1

[0022] Example 1 provides an environmentally friendly high-temperature-resistant refractory brick, which is composed of the following raw materials by weight percentage: flake graphite 13 wt%, modified fly ash 10 wt%, zirconia 2 wt%, composite binder 6 wt%, and the balance being magnesium oxide; The modified fly ash is prepared by the following process: (1) According to the mass ratio of fly ash to nitric acid solution 1:4, the fly ash is added to the nitric acid solution with a concentration of 1.1 g / mL and stirred for 5 h. After filtration, washing and drying, the active fly ash is obtained; (2) According to the usage ratio of active fly ash, dodecyl trimethyl ammonium bromide, scandium chloride and water 1 g:0.03 g:0.1 g:5 mL, the active fly ash, dodecyl trimethyl ammonium bromide and scandium chloride are added to water, and 4% ammonia water is added dropwise at 50 ℃ to adjust the pH to 6. After standing for 1 h, the modified scandium fly ash is obtained after filtration, washing and drying; (3) According to the mass ratio of scandium modified fly ash, lime slag and triethanolamine 1:0.09:0.04, the scandium modified fly ash, lime slag and triethanolamine are ball-milled and mixed uniformly, and then calcined at 600 ℃ for 2 h to obtain the modified fly ash. The scanning electron microscope image of the modified fly ash prepared in this example is shown in Figure 1 .

[0023] The composite binder is prepared by the following process: (a) According to the usage ratio of trimolybdenum dinitride, polydimethylsiloxane and methanol 1 g:18 mL:24 mL, trimolybdenum dinitride is first dispersed in methanol, then polydimethylsiloxane (average molecular weight: 115000) is added, ultrasonic treatment is carried out at 60 ℃ for 1 h, and then heated to 90 ℃ to remove the solvent to obtain modified trimolybdenum dinitride; (b) According to the mass ratio of modified trimolybdenum dinitride to thermosetting phenolic resin 1:6, the modified trimolybdenum dinitride and the phenolic resin are mixed uniformly to obtain the composite binder.

[0024] This embodiment also provides a method for preparing the above-mentioned environmentally friendly high-temperature refractory brick, the specific steps of which are as follows: Weigh out the raw materials for the above-mentioned environmentally friendly high-temperature refractory bricks. First, mix magnesium oxide, flake graphite, zirconium oxide and modified fly ash evenly. Then, add the composite binder and mix evenly. Put the mixture into a mold and pressurize it at 230 MPa for 4 min to obtain a brick blank. First, sinter the brick blank at 260 ℃ for 6 h, then raise the temperature to 720 ℃ for 4 h, and then raise the temperature to 1300 ℃ for 2 h to obtain the refractory brick.

[0025] Example 2 Example 2 provides an environmentally friendly high-temperature refractory brick, which is composed of the following raw materials by weight percentage: 12 wt% flake graphite, 8 wt% modified fly ash, 1 wt% zirconium oxide, 5 wt% composite binder, and the balance being magnesium oxide; The modified fly ash is prepared by the following process: (1) Fly ash was added to a nitric acid solution with a concentration of 1 g / mL and stirred for 4 h according to a mass ratio of fly ash to nitric acid solution of 1:3. After filtration, washing and drying, activated fly ash was obtained. (2) According to the ratio of active fly ash, dodecyltrimethylammonium bromide, scandium chloride and water, 1 g: 0.02 g: 0.1 g: 4 mL, add active fly ash, dodecyltrimethylammonium bromide and scandium chloride to water, add 3% ammonia water at 50 °C to adjust the pH to 6, let stand for 1 h, filter, wash and dry to obtain scandium modified fly ash; (3) The scandium-modified fly ash, lime slag and triethanolamine were ball-milled and mixed evenly according to the mass ratio of scandium-modified fly ash, lime slag and triethanolamine 1:0.08:0.03, and then calcined at 600 °C for 2 h to obtain modified fly ash.

[0026] The composite adhesive is prepared by the following process: (a) According to the ratio of molybdenum dinitride, polydimethylsiloxane and methanol 1 g: 15 mL: 20 mL, molybdenum dinitride was first dispersed in methanol, then polydimethylsiloxane (average molecular weight: 115000) was added, ultrasonically treated at 50 °C for 1 h, and then heated to 90 °C to distill off the solvent to obtain modified molybdenum dinitride; (b) The modified trimolybdenum nitride and the thermosetting phenolic resin were mixed evenly at a mass ratio of 1:5 to obtain a composite adhesive.

[0027] This embodiment also provides a method for preparing the above-mentioned environmentally friendly high-temperature refractory brick, the specific steps of which are as follows: Weigh out the raw materials for the above-mentioned environmentally friendly high-temperature refractory bricks. First, mix magnesium oxide, flake graphite, zirconium oxide and modified fly ash evenly. Then, add the composite binder and mix evenly. Put the mixture into a mold and pressurize it at 200 MPa for 3 min to obtain a brick blank. First, sinter the brick blank at 220 ℃ for 5 h, then raise the temperature to 700 ℃ for 3 h, and then raise the temperature to 1300 ℃ for 2 h to obtain the refractory brick.

[0028] Example 3 Example 3 provides an environmentally friendly high-temperature refractory brick, which is composed of the following raw materials by weight percentage: 15 wt% flake graphite, 12 wt% modified fly ash, 3 wt% zirconium oxide, 8 wt% composite binder, and the balance being magnesium oxide; The modified fly ash is prepared by the following process: (1) Fly ash was added to a nitric acid solution with a concentration of 1.2 g / mL and stirred for 6 h according to a mass ratio of fly ash to nitric acid solution of 1:5. After filtration, washing and drying, active fly ash was obtained. (2) According to the ratio of active fly ash, dodecyltrimethylammonium bromide, scandium chloride and water, 1 g: 0.05 g: 0.2 g: 6 mL, add active fly ash, dodecyltrimethylammonium bromide and scandium chloride to water, add 5% ammonia water at 60 °C to adjust the pH to 7, let stand for 2 h, filter, wash and dry to obtain scandium modified fly ash; (3) The scandium-modified fly ash, lime slag and triethanolamine were ball-milled and mixed evenly according to the mass ratio of scandium-modified fly ash, lime slag and triethanolamine 1:0.1:0.05, and then calcined at 700 ℃ for 3 h to obtain modified fly ash.

[0029] The composite adhesive is prepared by the following process: (a) According to the ratio of molybdenum dinitride, polydimethylsiloxane and methanol 1 g: 20 mL: 25 mL, molybdenum dinitride was first dispersed in methanol, then polydimethylsiloxane (average molecular weight: 115000) was added, ultrasonically treated at 70 °C for 2 h, and then heated to 100 °C to remove the solvent by distillation to obtain modified molybdenum dinitride; (b) The modified trimolybdenum nitride and the thermosetting phenolic resin were mixed evenly at a mass ratio of 1:8 to obtain a composite adhesive.

[0030] This embodiment also provides a method for preparing the above-mentioned environmentally friendly high-temperature refractory brick, the specific steps of which are as follows: Weigh out the raw materials for the above-mentioned environmentally friendly high-temperature refractory bricks. First, mix magnesium oxide, flake graphite, zirconium oxide and modified fly ash evenly. Then, add the composite binder and mix evenly. Put the mixture into a mold and pressurize it at 250 MPa for 5 min to obtain a brick blank. First, sinter the brick blank at 280 ℃ for 8 h, then raise the temperature to 750 ℃ ​​for 5 h, and then raise the temperature to 1400 ℃ for 3 h to obtain the refractory brick.

[0031] (ii) Comparative Example Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the modified fly ash is replaced with fly ash.

[0032] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that: when preparing modified fly ash, step (2) is omitted and scandium-modified fly ash in step (3) is replaced with active fly ash.

[0033] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the composite adhesive is replaced with phenolic resin.

[0034] (III) Test Examples The refractory bricks prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests.

[0035] Room temperature compressive strength test: The compressive strength of the refractory bricks in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 5072-2023 "Test method for room temperature compressive strength of refractory materials". The results are shown in Table 1.

[0036] High-temperature flexural strength test: The high-temperature flexural strength of the refractory bricks in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 3002-2017 "Test Method for High-Temperature Flexural Strength of Refractory Materials". The test conditions were 1400℃×0.5 h. The results are shown in Table 1.

[0037] Antioxidant test: Take the sample bricks prepared in Examples 1-3 and Comparative Examples 1-3 and record their mass as m0. Keep the sample bricks at 1400 ℃ in an air atmosphere for 10 h. After taking them out, record their mass as m1. Calculate the oxidation weight loss rate based on the mass change. The results are shown in Table 1.

[0038] Table 1. Test results of compressive strength, high-temperature flexural strength and oxidation weight loss of refractory bricks

[0039] As shown in Table 1, the environmentally friendly high-temperature refractory bricks prepared in Examples 1-3 of the present invention have excellent compressive strength, high-temperature flexural strength, and excellent oxidation resistance.

[0040] Compared to Example 1, Comparative Example 1 replaced modified fly ash with regular fly ash, and Comparative Example 2 replaced modified fly ash with lime slag-modified fly ash. The room temperature mechanical properties decreased slightly, while the high-temperature flexural strength and oxidation resistance decreased significantly. This indicates that adding modified fly ash to refractory bricks can optimize mechanical properties and improve high-temperature flexural strength and oxidation resistance. Specifically, fly ash has a high specific surface area and gel activity. After composite modification with scandium chloride and lime slag, the alkaline substances in the lime slag can activate the activity of fly ash and react with the silica and alumina to form a high-temperature resistant mineral phase. Scandium chloride loaded on the fly ash, reacting synergistically with the lime slag, can further enhance the gel activity of the fly ash, optimize its microstructure, purify impurities, reduce porosity, strengthen the bond between fly ash and the refractory brick matrix, improve sintering density, and enhance high-temperature strength and oxidation resistance.

[0041] Compared to Example 1, Comparative Example 3, which replaced the composite binder with phenolic resin, showed a slight decrease in antioxidant properties but a significant impact on mechanical properties. This indicates that using a composite binder can improve the mechanical properties of refractory bricks. Specifically, at low temperatures, the phenolic resin begins to pyrolyze under the catalysis of molybdenum dinitrate, forming an ordered graphitized network and strengthening the bonding effect. At medium temperatures, molybdenum dinitrate reacts with the matrix to generate carbides, enhancing interfacial bonding and strengthening the binder phase network, thus improving sintering quality. At high temperatures, the molybdenum compound forms a dense and stable antioxidant layer and creates a pinning effect in the matrix, improving the mechanical properties of the refractory bricks.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. Based on the present invention, some modifications or substitutions can be made, but these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of protection claimed by the present invention.

Claims

1. An environmentally friendly high-temperature-resistant refractory brick, characterized in that, The environment-friendly high-temperature-resistant refractory brick is composed of the following raw materials in percentage by weight: 12-15 wt% of flake graphite, 8-12 wt% of modified fly ash, 1-3 wt% of zirconia, 5-8 wt% of composite binder, and the balance of magnesium oxide; The modified fly ash is prepared by the following process: (1) adding fly ash into nitric acid solution, stirring, filtering, washing, and drying to obtain active fly ash; (2) adding the active fly ash, a surfactant, and scandium chloride into water, adjusting pH at 50-60 ℃, standing, filtering, washing, and drying to obtain scandium-modified fly ash; (3) ball-milling the scandium-modified fly ash, lime slag, and triethanolamine, and calcining to obtain the modified fly ash.

2. The environment-friendly high-temperature-resistant refractory brick according to claim 1, characterized in that, In step (1), the mass ratio of the fly ash to the nitric acid solution is 1:3-5, and the concentration of the nitric acid solution is 1-1.2 g / mL.

3. The environment-friendly high-temperature-resistant refractory brick according to claim 1, characterized in that, In step (2), the mass ratio of the active fly ash, the surfactant, and scandium chloride is 1:(0.02-0.05):(0.1-0.2), the surfactant is dodecyltrimethylammonium bromide, the pH is adjusted to 6-7, and the standing time is 1-2 h.

4. The environment-friendly high-temperature-resistant refractory brick according to claim 1, characterized in that, In step (3), the mass ratio of the scandium-modified fly ash, lime slag, and triethanolamine is 1:(0.08-0.1):(0.03-0.05), the calcining temperature is 600-700 ℃, and the calcining time is 2-3 h.

5. The environmentally friendly high-temperature-resistant refractory brick according to claim 1, characterized in that, The composite binder is prepared by the following process: (a) adding trimolybdenum dihalide and polydimethylsiloxane into methanol for ultrasonic treatment, and heating and distilling to obtain modified trimolybdenum dihalide; (b) mixing and stirring the modified trimolybdenum dihalide and phenolic resin to obtain the composite binder.

6. The environmentally friendly high-temperature-resistant refractory brick according to claim 5, characterized in that, In step (a), the amount ratio of the trimolybdenum dihalide to polydimethylsiloxane is 1 g:15-20 mL, and the heating and distilling temperature is 90-100 ℃.

7. The environmentally friendly high-temperature-resistant refractory brick according to claim 5, characterized in that, In step (b), the mass ratio of the modified trimolybdenum dihalide to phenolic resin is 1:(5-8), and the phenolic resin is thermosetting phenolic resin.

8. A method for preparing the environmentally friendly high-temperature-resistant refractory brick according to any one of claims 1-7, characterized in that, The process comprises the following steps: First, magnesium oxide, flake graphite, zirconia, and modified fly ash are uniformly mixed, then the composite binder is added and uniformly mixed, the mixture is loaded into a mold for pressure retention to obtain a green brick, and the green brick is gradient sintered and cooled to obtain the environment-friendly high-temperature-resistant refractory brick.

9. The method for preparing the environment-friendly high-temperature-resistant refractory brick according to claim 8, characterized in that, The pressure retention pressure is 200-250 MPa, and the pressure retention time is 3-5 min.

10. The method for preparing the environment-friendly high-temperature-resistant refractory brick according to claim 8, characterized in that, The gradient sintering process is: first sintering at 220-280 ℃ for 5-8 h, then sintering at 700-750 ℃ for 3-5 h, and then sintering at 1300-1400 ℃ for 2-3 h.

Citation Information

Patent Citations

  • Modified fiber refractory material and preparation method thereof

    CN104961477A

  • Graphite refractory material

    CN105541346A

  • Preparation process for producing high-grade ceramic by using pulverized coal cinder

    CN112125646A

  • Baking-free brick prepared from aluminum ash and preparation method of baking-free brick

    CN114907065A

  • High-temperature-resistant magnesia-carbon composite refractory brick and preparation method thereof

    CN120097714A